PABPN1 gene therapy for oculopharyngeal muscular dystrophy - A. Malerba (Nature Portfolio, 2017)
Oculopharyngeal muscular dystrophy is caused by trinucleotide repeat expansions in thePABPN1gene. Here the authors use AAV-based gene therapy to knockdown the mutant gene and replace it with a wild-type allele, and show effectiveness in mice and in patient cells.